Apakah Neraca Pembayaran Membatasi Pertumbuhan Ekonomi? - Kusuma, Arya Candra; Wardani, Aulia Pramudya; Amirudin, Amirudin; Yuliana, Rita (Seminar Nasional Official Statistics, 2024)
The balance of payments is one of the economic indicators related to various macroeconomic indicators. However, recent years have seen a deficit in the trade balance, a key component of the balance of payments. As per the thirlwall hypothesis, this may slow economic progress. Thus, Indonesia's balance of payments must be managed. This research tests the thirlwall theory and analyzes Indonesia's balance of payments drivers. Annual time series data from 1998-2022 was utilized. The findings confirm the thirlwall theory in Indonesia. The Autoregressive Distributed Lag (ARDL) model shows that GDP per capita and real interest rates negatively affect the balance of payments in the short and long run. The J-curve effect illustrates that the rupiah exchange rate negatively impacts the balance of payments in the near term but not in the long run. These findings may inform Indonesian balance of payments policy.